2021
DOI: 10.7150/ijms.51947
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA MSC-AS1 facilitates the proliferation and glycolysis of gastric cancer cells by regulating PFKFB3 expression

Abstract: Long non-coding RNA musculin antisense RNA 1 (lncRNA MSC-AS1) has been recognized as an oncogene in pancreatic cancer, hepatocellular carcinoma, nasopharyngeal carcinoma, and renal cell carcinoma. However, the functional significance of MSC-AS1 and its underlying mechanism in gastric cancer (GC) progression remain unclear. In this study, we demonstrated that the expression of MSC-AS1 in GC tissues was significantly higher than that in non-tumor tissues. Moreover, the elevated level of MSC-AS1 was detected in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…The human gastric cancer cell lines, AGS, SGC-7901, MGC-803, and MKN-45, and the gastric mucosal cell line, GES-1, were maintained and cultured under standard conditions in our lab 21 . The expression vectors, PSMD7-OE and RAD23B-OE, were constructed by inserting the cDNA products of PSMD7 and RAD23B into the pcDNA3.1(+) vector (V79020, Invitrogen, Carlsbad, CA, USA) and transfected into GC cells using Effectene transfection reagent (301427, Qiagen, Valencia, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The human gastric cancer cell lines, AGS, SGC-7901, MGC-803, and MKN-45, and the gastric mucosal cell line, GES-1, were maintained and cultured under standard conditions in our lab 21 . The expression vectors, PSMD7-OE and RAD23B-OE, were constructed by inserting the cDNA products of PSMD7 and RAD23B into the pcDNA3.1(+) vector (V79020, Invitrogen, Carlsbad, CA, USA) and transfected into GC cells using Effectene transfection reagent (301427, Qiagen, Valencia, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The proliferation of GC cells was assessed using the thiazolyl blue tetrazolium bromide (MTT) assay with the MTT reagent (CT02, Sigma-Aldrich) and the 5-ethynyl-2′-deoxyuridine (EdU) assay with the Cell-Light™ EdU Apollo®488 In vitro Imaging Kit (C10310-1, RiboBio, Guangzhou, China), as previously described 21 .…”
Section: Methodsmentioning
confidence: 99%
“…MSC-AS1 induces PGK1 expression and accelerates the progression of HCC ( 30 ). In addition, MSC-AS1 has a similar role in gliomas ( 31 ), gastric cancer ( 32 ), renal clear cell carcinoma ( 33 ), and pancreatic cancer ( 34 ). TMEM220-AS1, AC015908.3, AC009005.1, and AL031985.3 have been reported in a signature predictive of overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Linc-00475 also affects cancer progression via glycolysis. Jin et al have found that Linc-MSC-AS1 promotes the proliferation and glycolysis of gastric cancer cells by regulating the expression of PFKFB3 [20]. The study by Du et al has found that Linc-MIR210HG promotes aerobic glycolysis by regulating the expression of HIF-1α, which leads to the progression of triple-negative breast cancer [21].…”
Section: Discussionmentioning
confidence: 99%